User Opinion About the Inter Library Loan Services in Agricultural Science University Libraries in South India: An Evaluative Study - Kannappanavar, B. U.; Chidananda Swamy, H. M. (Journal of Information and Knowledge, 2011)
The study discusses about the inter library loan services provided by the agricultural science university libraries in South India. User opinion is collected and presented in the tables and the study found that very few users are satisfied with this service. Tables 6, 7 & 8 presented the data about the opinion of PG Students, Research Scholars and Faculty Members respectively. Opinion about Average time required for Receiving Books under Inter-Library Loan and Overall Satisfaction of Inter-Library Loan Services is discussed and found that 10% of the users are strongly satisfied with the service followed by 10% of users satisfied with the services and the remaining 80% of the users are not satisfied with this service.